L’activité de pêche artisanale au sud de la Méditerranée : gouvernance, dynamique socio-économique et enjeux environnementaux dans le port algérien de Jijel (Boudis) - Fouad Zaimen; Tarik Ghodbani; Hugo Vermeren (VertigO)
Fishing is one of the most important socio-economic activities in the Mediterranean and particularly in the Maghreb. In Algeria, it has become an employment sector for a large part of the coastal population in recent decades. The exploitation of the sea also represents one of the main animal protein resources for most coastal inhabitants. This paper is a contribution to the analysis of the socio-economic dynamics of fisheries in relation to two main aspects: the first is the governance mode of coastal natural resources, and the second is the context of fragility of the coastal ecosystems characterizing the Mediterranean Sea. This work is based on a study of the fishing port of Jijel (Boudis), considered as one of the most important fishing infrastructures of Eastern Algeria. This port has undergone profound transformations due to massive public investments for the development of port infrastructure as part of a national policy of economic recovery. Public actions have led to the broadening of the regional influence of the marketing of seafood products to consumers throughout the Eastern Algerian coastline as well as the interior territories. The modernization of the port has accompanied the improvement of the transport and the channels of resale of the fish resources; however, the governance of the fishing activity in Jijel fails to master the multiple ecological, economic and social constraints.